Improvement of corrosion resistance of AZ91D magnesium alloy by lanthanum-based conversion coating - Mohd Zamzuri, Mohammad Zain; Mokhtar, Mat Salleh; Norshah Afizi, Shuaib; S., Norbahiyah; Mohd Sabri, Hussin (SIRIM, 2011)
4th Malaysian Powder Metallurgy Symposium (MPMS) and Malaysian Metallurgical Conference (MMC) 2010 organized by SIRIM Berhad on 22nd - 23rd November 2010 at Parkroyal Hotel, Penang, Malaysia.